1999
DOI: 10.1016/s0032-3861(99)00041-5
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility of poly(vinylidene fluoride) and poly(methyl methacrylate-co-zinc polyacrylate) ionomers

Abstract: A random copolymer of methyl methacrylate and 5.7 mol.% of acrylic acid has been neutralized by zinc cation to different extents in order to study the effect of zinc carboxylate pendant groups on the miscibility of poly(methyl methacrylate) (PMMA) and poly(vinylidene fluoride) (PVDF). The interaction parameter (χ) has been calculated from the experimental depression of the PVDF melting point. χ is minimum at zinc carboxylate content of 2.8 mol.%. The dynamic mechanical analysis of the PVDF-PMMA ionomer binary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…When the content of TPU reached 25 wt%, PVDF appeared as a continuous phase while TPU appeared as a dispersed phase. Compared with immiscible PVDF/polycarbonate (PC) system [8] with obvious interface between two polymers, the blend (containing 25 wt% TPU) was considered as a partially miscible system. With the further increase in TPU content, there appeared to be two materials coexisting as the continuous phase.…”
Section: Microscopymentioning
confidence: 99%
“…When the content of TPU reached 25 wt%, PVDF appeared as a continuous phase while TPU appeared as a dispersed phase. Compared with immiscible PVDF/polycarbonate (PC) system [8] with obvious interface between two polymers, the blend (containing 25 wt% TPU) was considered as a partially miscible system. With the further increase in TPU content, there appeared to be two materials coexisting as the continuous phase.…”
Section: Microscopymentioning
confidence: 99%
“…In an attempt to utilize the tendency of PVDF to interact with polar polymers, several blend compatibility studies have been reported for blends of PVDF with a variety of ion-containing polymers [14]. Moussaif et al investigated the miscibility of PVDF with poly(methyl methacrylate-co-zinc acrylate) ionomers [15] and polycarbonate grafted with poly(methyl methacrylate-co-zinc acrylate) [16]. These studies showed an increasing tendency toward miscibility with an increase in the ionic functionality of the ionomer.…”
Section: Introductionmentioning
confidence: 99%
“…Once the size of the overlapped regions are larger than a certain dimension, for example, 10 nm, these regions constitute and behave as phase‐separated regions, exhibiting their own glass transition temperature ( T g 2 ) 18. Moussaif et al35 studied the miscibility between MMA‐ co ‐zinc acrylate copolymer and poly(vinylidene fluoride). The blends containing half‐neutralized copolymer exhibit miscibility and mechanical property better than those containing non‐neutralized and all‐neutralized copolymers.…”
Section: Resultsmentioning
confidence: 99%